Pengaruh Efektivitas Perputaran Piutang dan Perpustaran Kas terhadap Rentabilitas Ekonomi pada Koperasi Karyawan PT. Djarum Kudus - Ibrahim, Chanafi; Winahyuningsih, Panca; Thoha, Achmad (Lembaga Penelitian Universitas Muria Kudus, 2011)
The main problem in this study were 1) whether there is influence between the effectiveness of economic turnover to profitability in PT.Djarum Employees Cooperative Spirit? 2) whether there is influence between cash turnover effectiveness of economic Profitability on PT.Djarum Employees Cooperative Spirit?The purpose of this study were: 1) to examine the effect of turnover between the effective-ness of economic profitability at PT.Djarum Kudus Employees Cooperative, 2) to examine the effect of cash turnover between the effectiveness of economic profitability at PT.Djarum Kudus Employees Cooperative. Data collection methods used in this study is the documentation. That method of data collection by performing recording based on data obtained from the documents in PT.Djarum Employees Cooperative. With the results of this study as follows. 1.The effectiveness of accounts receivable turnover (X1) proved to have a positive and significant impact on economic profitability (Y) this is indicated from the results of the t test which proved the value of each regression coefficient 7.404 each variable is greater when compared with the value of t 2.920 t count table located in the area rejected (Ho), meaning that zero hypothesis (Ho) is rejected and alternative hypothesis (Ha) accepted. So the hypothesis presented in this study proved that the effectiveness of the accounts receivable turnover has a significant effect on economic profitability variables. 2.Effectiveness of cash turnover (X2) proved to have a positive and significant impact on eco-nomic profitability (Y) this is indicated from the results of the t test which proved the value of each regression coefficient 3.459 each variable is greater when compared with the value of t 2.920 t count table located in the area rejected (Ho), meaning that zero hypothesis (Ho) is rejected and alternative hypothesis (Ha) accepted. So the hypothesis presented in this study proved that the effectiveness of cash turnover has a significant effect on economic profitability variables.